HUBUNGAN KEPEMIMPINAN KEPALA SEKOLAH DAN PELAYANAN DENGAN KEPUASAN SISWA DI SMA NEGERI KABUPATEN BERAU - . Yusuf (Jurnal Paradigma (JP), 2019)
This research aimed to find out (1) relationship between headmaster’s leadership with student’s satisfaction, (2) relationship between service with student’s satisfaction, (3) relationship between headmaster’s leadership and service collectively with student’s satisfaction. Research method used in this research is quantitative method with correlation survey technique. The sampling technique used is multi stage random sampling. The responden in this research is Senior High School’s students in Berau Regency with population was 3486 students and sample was 171 students. The result of this research shows: First, there was a significant relationship between headmaster leadership with student’s satisfaction. Second, there was a significant relationship between service with student’s satisfaction. Third, there was a significant relationship between headmaster leadership and service collectively with student’s satisfaction.Keywords: Headmaster’s Leadership, Service, Student’s Satisfaction